Order and place in a colonial city : patterns of struggle and resistance in Georgetown, British Guiana, 1889-1924 - De Barros, Juanita (CEL - Canadian Publishers Collection., 2003)
Throughout the post-slavery Caribbean, former slaves and masters fought to determine the shape of the new free societies. Urban areas - with their growing populations and vibrant Afro-creole culture - were often the sites of these struggles. In Order and Place in a Colonial City Juanita De Barros explores the conflicting visions of public areas held by local political and economic elites and by non-white urban poor in Georgetown, British Guiana, demonstrating that the period of study was marked by class and racial tensions as the social and political landscape of the city changed significantly.